Study of dynamic behaviors for nano Fe-doped MgB2 superconductor via ac-susceptibility measurements. Issue 2 (1st February 2019) - Ansari, Intikhab A.
Abstract: Nano-sized superconducting polycrystalline particles of Mg1-x Fex B2 (0.00 ≤ x ≤ 0.04; space group P6/ mmm ) were synthesized through the solid state reaction route. The effect of nano-Fe substitution on ac -susceptibility at varying frequency range from 1 to 3 kHz in addition with ac -amplitude ( H ac ) and dc -applied field ( H dc ) were explored. The dynamical behavior of nano-particles shows the strong magnetic interaction between the nano-clusters with the increase of doping content. This is due to the successful inclusion of Fe 3+ ions in the matrix of MgB2 . X-ray powder diffraction (XRD) reveals the reduction of average grain size with increasing the doping level. Neel-Arrhenius (N-A) and Vogel-Fulcher (V-F) models were discussed to distinguish the dynamical behaviors of the nano-particles. Remarkably, the V-F model elucidates the experimental results much better than N-A model with the support of some parameters like jump attempt frequency, activation energy, magnetic anisotropy constant and V-F temperature.